Analysis of Sepak Sila Skills in the Kaimana Sepaktakraw Club, Bantaeng Regency - Nurlina; Rahmi, Silatul; Hasanuddin, M. Imran (Universitas Majalengka, 2025)
This research is a Descriptive Research, which aims to determine the description of the category of Sepak Sila Ability at the Kaimana Sepaktakraw Club, Bantaeng Regency. The population in this study were all members of the Kaimana Club totaling 27 people consisting of 21 men and 6 women. While the sample in this study were 15 male Kaimana club members who were selected by simple random sampling as representatives of the Kaimana Sepaktakraw Club, Bantaeng Regency. The data collection technique was obtained through testing and measuring Sepak Sila data. The data analysis technique used was percentage and analysis. The data from the research obtained the percentage of Sepak Sila Ability data from 15 people or (100%), very high category of 1 person or (7%), high category of 0 people or (0%), medium category of 9 people or (60%), low category of 5 people or (33%), and very low category of 0 people or (0%). Thus, it can be concluded that the percentage of the final data results of Sepak Sila Ability at the Kaimana Sepaktakraw Club, Bantaeng Regency is in the Medium category.